SISTEM INFORMASI MANAJEMEN SURAT BERBASIS WEB MENGGUNAKAN METODE EXTREME PROGRAMMING PADA KOREM 044/GAPO PALEMBANG - Sopiah, Nyimas; Alfarizki, Maulana Putra (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2023)
This study discusses a web-based mail management information system using the Extreme Programming method at Korem 044/Gapo Palembang. The system development method used in this study is the Extreme Programming (XP) methodology. There are four stages contained in the XP methodology, namely Planning, Design, Coding, and Testing. Observations, interviews, and literature studies are the techniques used to collect data in this study. The system design tool used in this study is the Unified Modeling Language (UML). Visual Studio Code and XAMPP are the main software for creating web programs. The testing method used in this research is the blackbox testing method. This research succeeded in producing a web-based mail management information system that was created using the Extreme Programming method for expensive use in the Infolahta Korem 044/Gapo Palembang.